2015
DOI: 10.18632/oncotarget.3584
|View full text |Cite
|
Sign up to set email alerts
|

Combination of carbon ion beam and gemcitabine causes irreparable DNA damage and death of radioresistant pancreatic cancer stem-like cellsin vitroandin vivo

Abstract: We try to elucidate whether a carbon ion beam alone or in combination with gemcitabine has advantages over X-ray in targeting putative pancreatic cancer stem-like cells (CSCs) in vitro and in vivo. Colony, spheroid formation and tumorigenicity assays confirmed that CD44+/ESA+ cells sorted from PANC1 and PK45 cells have more CSC properties than CD44−/ESA− cells. The number of colonies and spheroids formed from CSCs after carbon ion beam irradiation was significantly reduced compared to after X-ray irradiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 61 publications
(67 reference statements)
6
50
0
Order By: Relevance
“…In parallel, carbon-ion irradiation induces apoptosis-related Cytochrome C of triple negative breast CSCs [49]. In a pancreas cell line, heavy-ion irradiation induces irreparable clustered double strand breaks [50]. Data from clonogenic assays performed in our study showed a linear response with increasing doses with a unique alpha component.…”
Section: Discussionmentioning
confidence: 73%
“…In parallel, carbon-ion irradiation induces apoptosis-related Cytochrome C of triple negative breast CSCs [49]. In a pancreas cell line, heavy-ion irradiation induces irreparable clustered double strand breaks [50]. Data from clonogenic assays performed in our study showed a linear response with increasing doses with a unique alpha component.…”
Section: Discussionmentioning
confidence: 73%
“…As compared with photon irradiation, a higher percentage (2.4-fold) of GSCs stained positive for nuclear γ-H2AX 24 hours after carbon ion irradiation, demonstrating residual unrepaired double-strand breaks. Likewise, carbon ion irradiation increased persistent γ-H2AX foci as compared with photon irradiation in putative pancreatic stem cells (32,106). These results indicate that the sensitivity of cancer stem cells to carbon ions might exhibit an impaired capability of GSCs to repair carbon ion-induced DNA double-strand breaks.…”
Section: The Impact Of Carbon Ion Irradiation On Tumor Stem Cells Carmentioning
confidence: 80%
“…138,139,141 In light of the discussion above about some fraction of human tumor cells having higher RBE values because of DNA repair defects, one might ask whether CSCs have lower proton RBEs. Although the published data are scarce, it has been reported that CSCs may be more effectively killed by carbon ions compared to photons in colon and pancreas cancers both in vitro and in vivo, [142][143][144] and CSCs from colon and breast cancers may be more efficiently eliminated by proton irradiation than photon treatment, at least in vitro. [145][146][147] These latter findings suggest a higher RBE for CSCs and, hence, a potential therapeutic gain with protons over photon irradiations in tumors where CSCs are a significant resistant population.…”
Section: B Novel and Mechanistic Biology Studies To Quantify And Ementioning
confidence: 99%